The surface distribution and recyclability study on photodegradation methylene blue dye of immobilized TiO₂ under surfactant effect / Muhammad Syahirul Ikhwan … [et al.] - Ikhwan, Muhammad Syahirul; Nazeri, Nur Syazana; Natar, Nadiah Sabihah; Abdul Ghani, Nureel Imanina; Hamzah, Siti Raihan; Rosli, Muhammad Afiq; Mohd Ishak, Mohd Azlan; Mamauod, Siti Nur Liyana; Mohd Azami, Mohammad Saifuldin; Wan Ismail, Wan Izhan Nawawi (UiTM Press, 2022)
Immobilised titanium dioxide (TiO2) was prepared using commercially available carbon-doped TiO2 from Kronos VLP 7000 (Kronos). TiO2 was immobilised using a low amount of polyvinyl alcohol (PVA) as a polymer binder with various surfactants onto a glass plate as a support material using the double-sided adhesive tape (DSAT) technique. The photocatalytic activity of the immobilised TiO2 was evaluated by photocatalytic degradation of methylene blue (MB) dye. The prepared immobilised TiO2 without surfactant showed a poor coating with an uneven surface layer. In contrast, a significant surface improvement was observed by adding surfactant due to the dispersion of the PVA binder. The immobilised TiO2 with cetyltrimethylammonium bromide (CTAB) has shown better coating distribution and high adhesiveness compared with other surfactants. The XRD spectrum showed no phase transformation from anatase to rutile on immobilised TiO2 and TiO2-CTAB with an identical peak spectrum for both samples. PVA was represented by C-C, C-O, and O-H bonding peaks. In contrast, CTAB represented C-C bond stretching vibration, C-H bond stretching vibration, and C-N bond stretching functional vibration groups in immobilised TiO2-CTAB detected by FTIR analysis. The immobilised TiO2-CTAB shows good reusability and adhesiveness. It shows slightly lower photocatalytic activity with suspension mode TiO2 for the first three cycles. However, higher photoactivity was observed beyond the third cycle, nearly three times faster than TiO2 in suspension mode for the 8th-10th cycles. This might be due to the synergistic effect of CTAB that plays a role as surface distribution and pore-forming agent, making the increment of TiO2 surface active site to the reactant volume ratio.